2021
DOI: 10.1111/ctr.14249
|View full text |Cite
|
Sign up to set email alerts
|

Decline in renal function following intestinal transplant: is the die cast at 3 months?

Abstract: Introduction This study reports the incidence of chronic kidney disease (CKD) after intestinal transplant (IT) at a single, adult center in the United Kingdom. Methods A retrospective review of IT was undertaken. Methods of renal function assessment pre‐transplant were compared. Post‐transplant renal function and renal sparing strategies were analyzed. Results There was a 30% variation (p < .001) in estimated glomerular filtration rate (eGFR) and normalized GFR at assessment. In the first 3 months post‐transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…No simultaneous living kidney and intestinal donation was reported, probably by concern for donor safety. 41,42 There have been no reported deaths or major complications. [43][44][45][46][47][48] Wu et al reported in 40 donors 1 intraoperative bleeding, 1 small bowel obstruction (conservatively treated), and 1 incisional hernia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No simultaneous living kidney and intestinal donation was reported, probably by concern for donor safety. 41,42 There have been no reported deaths or major complications. [43][44][45][46][47][48] Wu et al reported in 40 donors 1 intraoperative bleeding, 1 small bowel obstruction (conservatively treated), and 1 incisional hernia.…”
Section: Discussionmentioning
confidence: 99%
“…However, based on the reported series, the overall risk of intestinal donation (segmental bowel resection) is limited and probably lower than that for kidney/liver donation. No simultaneous living kidney and intestinal donation was reported, probably by concern for donor safety 41,42 . There have been no reported deaths or major complications 43–48 .…”
Section: Discussionmentioning
confidence: 99%
“…This is described in detail previously. 27 Briefly, all patients received induction immunosuppression (alemtuzemab 30 mg and intravenous methylprednisone). A second dose of alemtuzemab was given on day 4 if there was no elevated risk of sepsis (collections, fistulas, or abdominal sepsis).…”
Section: Methodsmentioning
confidence: 99%
“…In IT recipients, the benefit of CNI minimization/sparing strategies appears to be limited in terms of preserving renal function. Rutter et al [ 75 ] in their single center study demonstrated significant decline in renal function irrespective of tacrolimus exposure. Herlenius et al [ 76 ], in their study of 10 IT recipients, noted that 4 patients were switched from CNI to sirolimus based regimen.…”
Section: Diagnosis and Management Of Ckd Post Non-kidney Sotmentioning
confidence: 99%